Production of Edible Film from Durian Seed Starch (Durio zibenthinus) as Biodegradable Plastic - Rustian, Zikra Putri; Dewata, Indang (Jurnal Kependudukan dan Pembangunan Lingkungan, 2022)
The edible film is a plastic that is easily degraded by microbes in the soil due to the presence of starch. The purpose of this study was to determine the effect of adding PEG-based carrageenan and determine the physical, mechanical, and biodegradable properties, and to compare it with the Japanese Industrial Standard (JIS) ZI707. The study was conducted using 4% PEG and variations in the addition of carrageenan concentrations of 0%, 0.5%, 1%, 1.5%, and 2%. The results of the physical properties test, the higher the concentration of addition of carrageenan, the higher the thickness value. The results of the tensile strength test showed that for the addition of 0% concentration the results obtained were 0.352 Mpa for 0.5% concentration, namely 0.568 Mpa, for 1% concentration, 0.746 Mpa, for 1.5% concentration, 1.047 Mpa and 2% concentration of 0.896 Mpa. For testing the mechanical properties, the optimum results were obtained with the addition of 1.5% carrageenan concentration with a tensile strength of 1.407 MPa and an elongation of 0.582%, and an elasticity of 403 MPa. The FTIR results show that there are no new functional groups from the test results